The Efficacy of Preoperative Tamsulosin on Ureteroscopy Access in Pediatrics: A Systematic Review and Meta-Analysis - Singgih, Nicholas Andrian; Oktaviani, Jacinda Risha; Pranowo Sampurno Secodiningrat, Raden Honggo; Adipurnama, William; Manuputty, Egi Edward; Tandarto, Kevin (Siriraj Medical Journal, 2023)
Objective: The incidence of urolithiasis in pediatrics increases to 4-10% annually. One of the methods for treating urolithiasis is ureteroscopy (URS). The small anatomy in pediatrics often makes the initial URS unsuccessful. Alpha blockers, a drug that can relax the ureteral muscles, is a therapy that can be considered before URS is carried out. The objective of this study is to evaluate the efficacy of preoperative tamsulosin for URS access in pediatrics. Materials and Methods: We conducted a search using four databases, including PubMed, EBSCO, Cochrane Library, and ProQuest. This study includes randomized controlled trials (RCTs), retrospective and prospective studies, which compared the efficacy of preoperative alpha blockers and placebo or non-placebo controls in pediatrics undergoing ureteroscopy. The outcome of interest was the success rate of URS access and the duration of surgery. Results: A total of 120 studies were identified from a database search. There were 3 studies included in this review involving 235 patients. The meta-analysis was conducted using a random-effects model. The results of the meta-analysis showed that alpha blockers provided a successful rate of ureteroscopy access in pediatric patients (Odds ratio (OR) 2.73; 95% confidence interval (CI) 1.52 up to 4.91; p=0.0008). Duration of surgery did not show significant results (Mean difference (MD) 3.46; 95% CI -3.59 up to 10.50; p=0.34).